PENGARUH PENGALAMAN KERJA TERHADAP KINERJA TENAGA KEPENDIDIKAN DI UNIVERSITAS PRIMA INDONESIA - Tuty Nainggolan (Politeknik Bisnis Indonesia, 2021)
This study aims to examine the effect of work experience on the performance of education personnel at the University of Prima Indonesia. This research is a survey research with a quantitative approach. The population in this study were education staff at Prima Indonesia University, totaling 104 education staff at Prima Indonesia University. Data collection techniques using a questionnaire. The results of the research by testing the hypothesis show that work experience with a t count value of 2,067 with a t table of 1,98397, obtained t arithmetic > t table (2,067 > 1,98397) partially significant effect on the performance of education personnel